Pedagogical Culture of Future Teachers of Musical Art: A Methodological Investigation - Pashchenko, Inna; Smakovsjkyj, Jurij; Martynjuk, Tetjana; Lesyk, Anzhelika (Journal of History Culture and Art Research, 2018)
The article deals with modern scholars’ approaches to the definition of the term “pedagogical culture of future teachers of musical art”. The authors give their own definition of future teacher’s pedagogical culture. It is defined as a subjectively conditioned system of values, culture-pedagogical knowledge, norms of behavior, which are practically implemented in the process of the development of a human being. These factors contribute to the realization of students’ abilities, development of moral and philosophical personal qualities by means of implementing certain pedagogical conditions of training in higher educational establishments of Ukraine. They also determine the choice of the correct strategy of specialists-educators’ cultural-pedagogical identity in their future professional activity. The criteria and levels as well as the stages of experimental work on the implementation of these methods have been identified and described. The experimental stages of the implementation of methods of formation of future teachers’ pedagogical culture by means of spiritual music have been identified and described. There are three stages: adaptive, cognitive-corrective, and acmeological. The results of experimental work, that demonstrate positive effects of the implementation of methods of formation of future teachers’ pedagogical culture by means of spiritual music in the educational process of pedagogical universities, have been also presented in the article.